Sleep deprivation: a mind-body approach. Issue 6 (November 2016) - Aguirre, Claudia C.
Abstract : Purpose of review: The purpose of this review is to summarize recent advances in our understanding of the impact sleep disturbances have on our health, with particular focus on the brain. The present review considers the influence of sleep disturbance on the neurovascular unit; the role of sleep disturbance in neurodegenerative diseases; and relevant strategies of neuro-immuno-endocrine interactions that likely contribute to the restorative power of sleep. Given the latest discoveries about the brain's waste clearance system and its relationship to neurodegenerative diseases like Alzheimer's disease, this review gives a brief overview on the molecular mechanisms behind sleep loss-related impairments. Recent findings: Recent evidence indicates that sleep plays a vital role in neuro-immuno-endocrine homeostasis. Sleep loss has been linked to elevated risks for cognitive and mood disorders, underscored by impaired synaptic transmission. The glymphatic system has been shown to be modulated by sleep and implicated in neurodegenerative disorders. Summary: Interactions between sleep quality, the immune system, and neurodegenerative disease are complex and a challenge to distil. These interactions are frequently bidirectional, because of sleep's characterization as an early symptom and as a potential factor contributing to the development and progression of mood and cognitive disorders. Video abstract: http://links.lww.com/COPM/A18 Abstract : Supplemental Digital Content is available in the text